PM10-bound polycyclic aromatic hydrocarbons in Chiang Mai (Thailand): Seasonal variations, source identification, health risk assessment and their relationship to air-mass movement - Wan Wiriya (2018)
This study aims to analyze the seasonal variations of PM10-bound polycyclic aromatic hydrocarbons (PAHs) for an estimation of the human health risk and identification of their possible sources. Ninety four PM10 samples were collected during the dry and wet seasons of 2010 and the dry season of 2011 in Chiang Mai, Thailand, and analyzed for 16 PAHs by gas chromatography-mass spectrometry. The average PM10 concentrations were 104.91±32.70, 13.28±11.34 and 36.24±19.16μg/m3in dry season of 2010, wet season of 2010 and dry season of 2011, respectively, while the average 16-PAHs concentrations were 25.87±10.13, 3.12±2.18 and 4.58±2.18ng/m3, respectively. Correlations of PM10 and total PAHs concentrations were relatively high during all seasons (r>0.796). In addition, PM10 concentrations were highly correlated with carcinogenic PAHs (r=0.927) during the dry season of 2010, indicating that carcinogenic compounds were dominant in the particulate PAHs and could be generated from open burning, usually conducted in the dry season. The average PM10 concentration in the dry season of 2011 was much lower than that in 2010 and lower than the annual average of the past 12years (48.17μg/m3) because of the unusually high amount of rain precipitation and low open burning activity in this year. According to the accumulated number of hot spots occurring in northern part of Thailand, approximately 19,000 spots were found in the dry season of 2010, while only 6,600 spots were found in the dry season of 2011. It can be seen that larger scale open burning activities were performed in the dry season of 2010 than in the dry season of 2011. The value of toxicity equivalent concentration from PAHs in the dry season of 2010 was higher than that of the wet season of 2010 and the dry season of 2011. This is obviously related to concentrations of PM10 and PAHs. Diagnostic ratio and principal component analysis were used to find out the sources of PM10-bound PAHs. It was found that vehicle emission and biomass burning were the main sources of PM10 and PAHs in this area. The high ratio value of benzo(a)anthracene/chrysene (BaA/CHR) in the dry season of 2010 indicated possible photochemical processes and long distance emissions. Findings on source identification of PM10 and PAHs were found to be relevant to the direction and speed of air mass movement run by backward trajectory. © 2013 Elsevier B.V.